Alterações histopatológicas de placentas e cordões umbilicais - Klank, Francisco Albuquerque (2018)
Introduction: Gestational Hypertensive Syndromes (SHG) continue to be a major cause of direct morbidity and mortality in Brazil, with a high proportion in the North. Even with several health policies created to try to curb maternal morbidity and mortality, scientific data indicate that there is still a need for scientific studies, especially histopathological ones. Objective: To evaluate the histopathological changes in human placentas and umbilical cords, of parturients with SHG. Methodology: The research was carried out at the High-risk Maternity Our Lady of Lourdes, Aracaju-SE. The sample consisted of 28 pregnant women with SHG, distributed in 4 groups: Normotensive Pregnant Women, Gestational Hypertension, Chronic Hypertension and the group with Pre-eclampsia, totaling 7 pregnant women per group. The data were analyzed by the statistical program Grad pad prism, with significant data (<0.05), using the one-way Anova and Tukey's multiple comparison test. The placentas and umbilical cords were submitted to 4 different methodologies, beginning with the histological processing - light microscopy, then histopathological analyzes of placentas by Hematoxylin and Eosin - HE, histopathological analyzes of the placentas following the staining technique with Masson and histopathological analyzes of the placentas. placentas following the Coloring Technique - PAS. Results: After analyzing the histological images, it was possible to identify in the placentas of normotensive pregnant women the mature and flat decidua with eosinophilic tissue and presence of fibrin, with dense epithelium and intact villi. The chorionic villi presented quite vascularization, with knots and scions. The umbilical cord presented an artery with an intimate and muscular layer of usual thickness. As for the placentas of patients with gestational hypertension, the smooth muscle thickening of the placental vessels, microcalcifications and vessel hyalinization were observed, in addition it was observed aged areas and areas with hyaline degeneration in the villi. In the placentas of pregnant women with chronic hypertension, hyalinization and aging of the villi were found, with microcalcification and hemorrhagic foci. The umbilical cord of pregnant women with chronic hypertension presented thick muscle wall, vessel hyalinization and cell degeneration. In the placentas of pregnant women with mild preeclampsia it was possible to observe intense groupings of degenerated and hyalinized villi. The umbilical cord presented thickening of the muscular layer. The placentas of pregnant women with severe pre-eclampsia were able to observe hyalinization of the villi, severe groupings with focus of calcification and hemorrhagic areas. Finally, it was identified that pregnant women in adulthood acquired SHG; the newborns of pregnant women with chronic hypertension were those that suffered the greatest impact of the syndrome, presenting slight decrease in weight, height, thoracic perimeter and cephalic perimeter. The placentas and umbilical cords of pregnant women with SHG presented structural changes and involvement of the tissue structures when compared to the normotensive pregnant women group. Conclusion: In this sense, it is concluded that the gestational annexes with SHG have structural and cellular changes at the placental and umbilical cord level, chronic hypertension is called attention, the data are conclusive, in addition, the placenta and umbilical cord of pregnant women with SGH, are an inexhaustible source of important scientific production on gestational development, and may contribute actively to the clinical findings of pregnant women and the newborn.